Bioethanol PRODUKSI BIOETANOL DARI BIJI SORGUM (Sorghum bicolor) MELALUI PROSES HIDROLISIS ENZIMATIS - Supriyanti, Arni; Pramana, Yanuar Sigit; Widiyanti, Palupi Tri; Pudjianto , Karyawan (Jurnal Agroindustri, 2023)
Production of carbohydrate-based bioethanol using raw materials derived from starch requires pre-processing. The pretreatment and hydrolysis process of sorghum grains from various sorghum varieties has not been extensively studied in the context of fermenting sorghum into bioethanol. The purpose of the research is to obtain the fermentation conditions so that the bioethanol yield was optimal and could also produce other useful products. The research employed an experimental design, and process efficiency was evaluated based on parameters such as Sugar Consumption Ratio (SCR) and Fermentation Ratio (FR). The concentration of the glucoamylase enzyme was set at 0.2% relative to the total solid (TS) content. The yeast Saccharomyces cerevisiae strain Hakken I was used at a concentration of 10% of the fermentation volume. Additional nutrients included NPK (0,012) and Urea (0,072 %). The liquefaction process occurred at temperatures between 80-90°C for one hour, followed by saccharification at temperatures between 55-60°C for two hours. Fermentation was conducted at temperatures ranging from 28-32°C for a duration of 60 hours. The results revealed that the total sugar content (TS) of the raw materials ranged from 69% to 73% for several sorghum varieties tested. The Sorghum Numbu variety exhibited the highest TS value at 72,81%. Furthermore, the highest process efficiency was achieved with the Numbu sorghum variety, yielding an FR of 86,69% and an SCR of 87,39%.